Relevansi Pendekatan Bimbingan dan Konseling di Era Digital: Studi Kasus Cyberbullying - Devitasari, Devitasari; Khoiriyah Isnaini Firmansyah Putri; Resi Hiskawiyah SW; Hantika Melistianti; Ahman, Ahman; Ibrahim Al Hakim (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2025)
Cyberbullying poses a serious threat to adolescent mental health in the digital age. This study aims to analyze the psychological impact of cyberbullying and formulate appropriate Guidance and Counseling (BK) interventions through a study of adolescents. Using qualitative methods with documentary study techniques, the results indicate that victims experience severe psychological distress, including anxiety, depression, and social isolation. The main findings of this study confirm that a BK approach based on Cognitive Behavioral Therapy (CBT) is the most relevant intervention to address these psychological impacts. Cognitive restructuring techniques in CBT have proven effective in restoring victims' self-esteem and building empathy for cyberbullying perpetrators. This study also recommends the integration of online cyber-counseling services and the enhancement of school counselors' digital competencies as adaptive responses to adolescent mental health challenges in the digital age. This intervention is expected to provide effective psychological support and promote the recovery of cyberbullying victims.